Edward Bartlett (1844–1908). Biography, Bibliography and Contributions to the Herpetology of Borneo - Aaron M., Bauer; Indraneil, Das (Society for the Study of Amphibians and Reptiles, 2024)
This facsimile of the herpetological works of Edward Bartlett commemorates the Tenth World Congress of Herpetology, held 5–9 August 2024 at Kuching, Sarawak, Malaysia. The present volume brings together the collected herpetological works of Edward Bartlett, who served as the curator of the Sarawak Museum in Kuching from 1893 to 1897. Bartlett was primarily an ornithologist, but his work in Borneo covered many areas of zoology. His herpetological output comprised a single substantial paper on lizards and crocodiles and a series of small papers on snakes, chelonians and amphibians initially published in the Sarawak Gazette and subsequently reprinted in book format. Bartlett’s life and professional career have remained poorly documented and have been the subject of many contradictory statements in the literature. In this book, a thorough biography of Bartlett and a complete bibliography of his scientific publications are presented for the first time, along with an evaluation of his contributions to the herpetology of Borneo and the development of the Sarawak Museum. Facsimile reprints are provided of all of Bartlett’s herpetological papers as well as two short, related notes by other authors. Finally, an up-to-date checklist of the amphibians and reptiles of Borneo is presented and compared with Bartlett’s enumeration of the herpetofauna almost 130 years ago.